The Deconstruction of Dark Academia Through Diasporic Alienation in R.F. Kuang’s Babel, or The Necessity of Violence - Salsabilla Zahran Galuh Putri Subawati, Lili Awaludin, R. Myrna Nur Sakinah (Journal of Educational Studies, 2025)
This study analyses Babel, or The Necessity of Violence, by R.F. Kuang as its material object, focusing on how the novel represents diasporic alienation and critiques the romanticization of dark academia within Western elite academic spaces. The research addresses two main problems: (1) how diasporic alienation is constructed within elite academic institutions, and (2) how the novel exposes the ideological mechanisms behind the aestheticization of dark academia. To answer these questions, this study employs a postcolonial framework, drawing on Homi K. Bhabha’s concepts of hybridity, mimicry, and the third space, alongside Michel Foucault’s theory of discourse and power/knowledge. Using a qualitative descriptive method, the research analyses selected textual excerpts through close reading to identify recurring discursive patterns related to identity, institutional power, and knowledge production. The findings consist of 6 data points that indicate that diasporic alienation in the novel is portrayed as a structural condition characterized by ambivalence, identity fragmentation, and conditional acceptance, in which diasporic subjects are simultaneously included and marginalized within the academic system. Furthermore, the study reveals that the novel critiques dark academia by dismantling its central assumptions, particularly the myth of neutrality in academia, the hierarchical production of knowledge, and racial exclusion. Academic institutions are thus depicted not as neutral sites of intellectual pursuit, but as mechanisms that reproduce colonial power relations while masking them through aesthetic and ideological practices. Therefore, Babel, or The Necessity of Violence, functions as a critical literary intervention that challenges both the epistemic authority and the romanticized representation of Western academia.